1968
DOI: 10.1070/pu1968v011n03abeh003927
|View full text |Cite
|
Sign up to set email alerts
|

The Cosmological Constant and the Theory of Elementary Particles

Abstract: A 6-dimensional grand unified theory with the compact space having the topology of a real projective plane, i.e., a 2-sphere with opposite points identified, is considered. The space is locally flat except for two conical singularities where the curvature is concentrated. One supersymmetry is preserved in the effective 4d theory. The unified gauge symmetry, for example SU(5) , is broken only by the non-trivial global topology. In contrast to the Hosotani mechanism, no adjoint Wilson-line modulus associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
210
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 530 publications
(220 citation statements)
references
References 12 publications
8
210
1
1
Order By: Relevance
“…This cosmic acceleration has been attributed to a dark energy component with negative pressure. While the simplest model for dark energy is the cosmological constant, it suffers from a fine-tuning and coincidence problems (Zeldovich 1968;Weinberg 1989). In this paper, we explored power-law cosmologies that have the potential of explaining various cosmological data, such as supernovae of type Ia, the age of the universe and the primordial nucleosynthesis.…”
Section: Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…This cosmic acceleration has been attributed to a dark energy component with negative pressure. While the simplest model for dark energy is the cosmological constant, it suffers from a fine-tuning and coincidence problems (Zeldovich 1968;Weinberg 1989). In this paper, we explored power-law cosmologies that have the potential of explaining various cosmological data, such as supernovae of type Ia, the age of the universe and the primordial nucleosynthesis.…”
Section: Final Remarksmentioning
confidence: 99%
“…While cosmological constant remains the simplest explanation of cosmic acceleration, it suffers from an impressive fine-tuning and the coincidence problem (Zeldovich 1968;Weinberg 1989). Given this, dynamical fields are usually invoked, such as quintessence (Ratra & Peebles 1988;Frieman et al 1995;Caldwell et al 1998;Zhu 1998;Zhu et al 2001;Sahni & Starobinsky 2006), phantom fields (Caldwell 2002;Alcaniz 2004;Nesseris & Perivolaropoulos 2004;Scherrer 2005), quintom (Feng et al 2005;Wu & Yu 2005) and Chaplygin gas (Kamenshchik et al 2001;Bento et al 2002;Bilic et al 2002;Dev et al 2003Dev et al , 2004Zhu 2004;.…”
Section: Introductionmentioning
confidence: 99%
“…Johnson and Walker (2005) reported that Sir Michael asserted that "…understanding space is the fundamental problem of physics, and his talk focused extensively on the relationship between mathematics and physics, particularly with regard to the nature of space.". Over the years many researchers have been preoccupied with the true nature of the emptiness that is space and its connection to the problem of gravity, among them Sakharov (1967), Zel'dovich (1967), Misner, Thorn and Wheeler (1971), Puthoff (2001), and Wüthrich (2005) to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…We are therefore left with the second cosmological problem of how to explain the low "incremental" positive value observed today. A first original idea has been historically proposed in Zel'Dovich (1967);Zel'dovich (1968), considering ρ Λ as being gravitational interaction energy between virtual pairs of the quantum electrodynamic (QED) vacuum. Unfortunately, this elegant propositon could still not explain the low value of the possible cosmological constant.…”
Section: Introductionmentioning
confidence: 99%